OMEGA - OSIRIS mapping of emission-line galaxies in A901/2: III. - Galaxy properties across projected phase space in A901/2 - Weinzirl, Tim; Aragón-Salamanca, Alfonso; Gray, Meghan E.; Bamford, Steven P.; Rodriguez Del Pino, Bruno; Chies-Santos, Ana L.; Böhm, Asmus; Wolf, Christian; Cool, Richard J. (Oxford University Press, 2017)
We conduct a comprehensive projected phase-space analysis of the A901/2 multicluster system at z ∼ 0.165. Aggregating redshifts from spectroscopy, tunable-filter imaging and prism techniques, we assemble a sample of 856 cluster galaxies reaching 108.5 M⊙ in stellar mass. We look for variations in cluster galaxy properties between virialized and non-virialized regions of projected phase space (PPS). Our main conclusions point to relatively gentle environmental effects, expressed mainly on galaxy gas reservoirs. (1) Stacking the four subclusters in A901/2, we find galaxies in the virialized region are more massive, redder and have marginally higher Sérsic indices, but their half-light radii and Hubble types are not significantly different. (2) After accounting for trends in stellar mass, there is a remaining change in rest-frame colour across PPS. Primarily, the colour difference is due to the absence in the virialized region of galaxies with rest frame B − V < 0.7 and moderate-to-high (M⋆ > 109.85 M⊙) stellar mass. (3) There is an infalling population of lower mass (M⋆ ≤ 109.85 M⊙), relatively blue (B − V < 0.7) elliptical or spheroidal galaxies that are strikingly absent in the virialized region. (4) The number of bona fide star-forming and active galactic nucleus galaxies in the PPS regions is strongly dictated by stellar mass. However, there remains a reduced fraction of star-forming galaxies in the centres of the clusters at fixed stellar mass, consistent with the star formation–density relation in galaxy clusters. (5) There is no change in specific Hα-derived star formation rates of star-forming galaxies at fixed mass across the cluster environment. This suggests that pre-processing of galaxies during infall plays a prominent role in quenching star formation.